SCALS: a fourth-generation study of assisted living technologies in their organisational, social, political and policy context. Issue 2 (15th February 2016) - Greenhalgh, Trisha; Shaw, Sara; Wherton, Joe; Hughes, Gemma; Lynch, Jenni; A'Court, Christine; Hinder, Sue; Fahy, Nick; Byrne, Emma; Finlayson, Alexander; Sorell, Tom; Procter, Rob; et al.
Abstract : Introduction: Research to date into assisted living technologies broadly consists of 3 generations: technical design, experimental trials and qualitative studies of the patient experience. We describe a fourth-generation paradigm: studies of assisted living technologies in their organisational, social, political and policy context. Fourth-generation studies are necessarily organic and emergent; they view technology as part of a dynamic, networked and potentially unstable system. They use co-design methods to generate and stabilise local solutions, taking account of context. Methods and analysis: SCALS (Studies in Co-creating Assisted Living Solutions) consists (currently) of 5 organisational case studies, each an English health or social care organisation striving to introduce technology-supported services to support independent living in people with health and/or social care needs. Treating these cases as complex systems, we seek to explore interdependencies, emergence and conflict. We employ a co-design approach informed by the principles of action research to help participating organisations establish, refine and evaluate their service. To that end, we are conducting in-depth ethnographic studies of people's experience of assisted living technologies (micro level), embedded in evolving organisational case studies that use interviews, ethnography and document analysis (meso level), and exploring the wider national and international context for assisted living technologies and policy (macro level). Data will be analysed using a sociotechnical framework developed from structuration theory. Ethics and dissemination: Research ethics approval for the first 4 case studies has been granted. An important outcome will be lessons learned from individual co-design case studies. We will document the studies' credibility and rigour, and assess the transferability of findings to other settings while also recognising unique aspects of the contexts in which they were generated. Academic outputs will include a cross-case analysis and progress in theory and method of fourth-generation assisted living technology research. We will produce practical guidance for organisations, policymakers, designers and service users.